High-resolution numerical modelling reveals tsunami risk hotspots in Xiamen City, China - Shi, Xianwu; Dong, Dibo; Ye, Zuchao; Huang, Junbao; Ying, Chao; Li, Xurui; Yan, Yuhan; Ding, Yiting (Frontiers in Marine Science, 2024)
Tsunamis, generated by submarine earthquakes, landslides, or volcanic eruptions, are a significant hazard to coastal areas owing to their sudden onset and rapid propagation speed. Thus, tsunami disaster risk assessment is crucial to determine potential losses and severity of future tsunami impacts, providing essential support for disaster prevention and mitigation efforts. This study presents a case study of Xiamen City in Fujian province for developing a high-precision tsunami model. Utilizing nearshore water depth and digital elevation model data, we established a high-resolution tsunami numerical simulation model for Xiamen City that accounts for the impact of water overrunning levees and overshoals. Historical tsunami disaster records were used to validate the numerical model. By determining multiple tsunami source scenarios that could potentially affect the counties of Xiamen City, we simulated the inundation range and water depth distribution required for the potential maximum tsunami event. The simulation results facilitated a tsunami hazard assessment. Considering land use and important tsunami-affected exposures including industrial and chemical enterprises and ports, we evaluated the vulnerability of Xiamen City to tsunami disasters. Based on the determination of hazard and vulnerability levels, we investigated the risk distribution of tsunami disasters in Xiamen City. The results of this study lay the groundwork for developing methodologies to improve tsunami disaster risk assessment in coastal areas.